Efficacy and success rate of Distal Radial Artery Access at the Anatomical Snuffbox for Coronary Intervention at Central Chest Institute of Thailand - Kamonrat Thongplung; Chanikarn Kanaderm; Jutatip Na Witayanan; Anek Kanoksilp; Thamarath Chantadansuwan (BMC Cardiovascular Disorders)
Abstract Background Distal radial artery access, which involves puncturing the radial artery at the anatomical snuffbox, is increasingly being adopted in interventional cardiology. This approach offers several advantages over traditional standard transradial access, including improved procedure positioning, a lower incidence of radial artery occlusion, and shorter hemostasis. Objective To study the benefit of distal radial access during coronary angiography (CAG) or percutaneous coronary intervention (PCI) with palpation technique in terms of success rate, first attempt success, number of attempts, time to access, and complications. Method A prospective cohort study was performed between June 2022 and June 2023. Two hundred thirty-three patients received coronary intervention by three experienced transradial operators through right or left distal radial access. Result The mean age of patients was 62.9 years old. 58% of patients were male. Most patients had chronic coronary syndrome (35.6%), valvular heart disease (30.9%), and acute coronary syndrome (24.9%). The most used site was the right distal radial artery, and 6 Fr sheaths were mainly used. The median diameter of the distal radial artery measured by ultrasound was 0.26 (0.23–0.28) cm. First attempt success rate was 171 (73.4%). The median number of attempts was one (1.0–2.0). The median time to access the distal radial access was 1.15 (0.57–1.64) min. Puncture times were stabilized and improved after a higher number of procedures. Access site crossover was 25 (10.7%), mainly performed via the right radial artery 18 (7.7%). However, ultrasound guidance for bailout situations during puncture was done in 10 (4.3%), which achieved successful cannulation. The success rate of distal radial cannulation by palpation technique was 201(86.3%), and the overall success rate after the ultrasound-guided bailout situation was 211 (90.6%). There were 34 (14.6%) minor hematomas after the procedures, and one patient had thumb numbness. Conclusion Distal radial access at the anatomical snuffbox is an effective and viable alternative for coronary interventions in patients with a favorable radial pulse, demonstrating a high success rate. Ultrasound-guided puncture is an important bailout strategy when blind palpation appears difficult, significantly improving procedure success and reducing complications.